The huge effect of Mn substitution on the structural and magnetic properties of LaFeAsO: the La(Fe, Mn)AsO system. (21st December 2018) - Martinelli, A; Manfrinetti, P; Provino, A; Ritter, C; Ferdeghini, C
Abstract: The substitution of Mn for Fe on the sub-lattice in LaFeAsO has a remarkable impact on both structural and magnetic properties; for example, the structural and magnetic transition temperatures decrease of 20 K in samples with a Mn-content as low as x = 0.01. Such a dramatic effect results from the high stability of the substituting Mn 2+ ion (3 d 5 ) in its high-spin state, which opposes any variation to its electronic state (configuration), perturbing thereby interactions within the Fe sub-lattice between the Fe ions surrounding the substituent. Several investigations ascertained that the structural transformation in Ln FeAsO compounds ( Ln : lanthanide) cannot be ascribed to lattice degrees of freedom, but rather to electronic or spin ones. In this context, even an extremely low concentration of Mn 2+ ions diluted in the Fe sub-lattice produces a reduction of the electronic degree of freedom of the system, thus hindering the structural transformation and the magnetic transition.